Techno-economic optimization of a geothermal ORC with novel "Emeritus" heat rejection units in hot climates. (March 2020) - Astolfi, M.; La Diega, L. Noto; Romano, M.C.; Merlo, U.; Filippini, S.; Macchi, E.
Abstract: The present work aims to investigate the potential advantages in using a novel wet and dry configuration for heat rejection units in ORC power plants. The reference case is a geothermal power plant that exploits a low temperature brine and uses a closed loop of cooling water to release the condensation heat to the ambient. In the calculations, the off-design operation of the whole plant is optimized from a techno-economic point of view with a realistic part-load behavior of the ORC and the use of experimentally validated correlations for the heat rejection section. The performance attainable with the novel LU-VE Emeritus® unit equipped with a water spray system and adiabatic panels is compared with those achievable with the same unit in dry operation. Final results show a marked increase of electricity production as well as of revenues with Emeritus® units with respect to a dry unit. Highlights: We studied the off-design behavior of different geothermal ORC. We compared the novel Emeritus heat rejection units and conventional dry air coolers. We optimized the whole system from a techno-economic point of view. We highlighted the advantages in adopting wet and dry heat rejection units. We analyzed the impact of perforation cost on system optimal design.